Analysis and Optimization of the High-Voltage Rewinding Process in Electric Motors and Generators to Improve Performance and Energy Efficiency - Ramli Adi Putra; Chairul Gagarin Irianto; R. Deiny Mardian W (Eduvest - Journal of Universal Studies, 2026)
Motors and generators play a very important role in the industrial sector. These machines often fail due to overload, poor power quality, or internal winding faults, which necessitate rewinding efforts. Analysis And Optimization Of The High-Voltage Rewinding Process In Electric Motors And Generators To Improve Performance And Energy Efficiency refers to the process of rewinding the coil windings in an electric motor or generator when the original winding is damaged, the insulation quality has deteriorated, or the machine experiences malfunction. This process should include analytical procedures that can predict and estimate the efficiency of rewound motors and generators, helping energy managers make more cost-effective decisions. The purpose of this study is to analyze the effect of the rewinding process on high-voltage electric motors and generators in relation to energy performance and efficiency, as well as to evaluate its impact on system reliability and operational performance. The research methodology for motors and generators includes several stages: testing, dismantling, data collection, repair, coil fabrication, coil testing, coil insertion, varnishing, oven curing, assembly, and final testing. After rewinding, efficiency and performance analyses were conducted during the no-load and load tests to compare conditions before and after the rewinding process of the motor and generator. The results indicate that after rewinding, performance targets were achieved, including improved energy efficiency and enhanced motor or generator performance, as demonstrated by test results before and after rewinding. Additionally, the no-load and load test results met acceptable standards for vibration, current (amperage), voltage, and power.